Telling Women’s Stories in 16th-Century Central Asia: A Book of Guidance in Chaghatay Turkic for a Royal Lady of the Bukharan Court - DeWeese, Devin (Oriens, 2015)
This study explores a substantial work in Chaghatay Turkic produced in Bukhārā in the early 16th century for ʿĀʾisha Sulṭān Khānïm, wife of the ‘Uzbek’ Chinggisid ruler ʿUbaydullāh (nephew of Muḥammad Shïbānī Khān). The work, written by a certain Maḥmūd Andkhūdī, survives in a unique manuscript in Paris, but hitherto has not drawn scholarly attention (due to the misleading catalogue description, from the 1930s); it offers anecdotal commentaries and illustrations for a selection of Qurʾānic verses, and the stories used to explain and expand upon the religious principles have in common a focus on issues regarded as of importance to women.